Choose Music! A Consulting and Training Strategy for Admission to Higher Education in Music - Duţică Luminiţa (Sciendo, 2019)
The educational project CHOOSE MUSIC!, subtitled "for counselling and training for admission to higher education in music", was created many years ago, at the initiative of Prof. Univ. PhD. Luminiţa Duţică, with the main purpose of creating a bridge between the pre-university and academic musical education (through pupils - students, pupils - university professors, etc.). Another special objective was to promote the image and opportunities existing at "George Enescu" National University of Arts of Iași. In this respect, inter-institutional partnerships were established between the Faculty of Interpretation, Composition and Theoretical Music Studies within "George Enescu" National University of Arts of Iași and numerous art high schools/colleges, especially from the regions of Moldavia (Suceava, Botoșani, Bacău, Piatra-Neamț, Iași, Bârlad and Galați). In this study we will go into more detailed aspects related to teaching and art activities made for this purpose, diverse and attractive, evidenced by: demonstration lessons of Music theory, Classical composition / jazz - easy listening, Musicology, Choral/Orchestral Conducting, MasterClass for aspects regarding the perception and graphic representation of the sounds, as well as the specific musical skills training (held by professors Luminiţa and Gheorghe Duţică), to which educational concerts, book launches, special meetings with teachers from the pre-university education, additional training with students for admission to the academic musical education in Iași (especially in the contest subject called Theory - Solfeggio -Melodic Dictation.